Ticagrelor-induced thrombotic thrombocytopenic purpura: A case report and review of the literature. Issue 26 (June 2018) - Wang, Xiaoya; Zhang, Shufang; Li, Leiqing; Hua, Junjie; Zhu, Lei; Li, Libin; Zhang, Gensheng
Abstract: Rationale: Ticagrelor, a new type of P2Y12 receptor antagonist, has been highly recommended to be used in acute coronary syndrome by the latest guideline, but its side effects are not well-known. We seek to illustrate a potential fatal condition, thrombotic thrombocytopenic purpura (TTP), caused by ticagrelor. Patient concerns: An 87-year-old man who had been prescribed with ticagrelor for 2 months after ST-elevation myocardial infarction (STEMI), presented with severe thrombocytopenia, anemia, renal and liver dysfunction, heart failure and fever. Diagnoses: Peripheral blood smear showed schistocytosis, and a disintegrin and metalloproteinase with thrombospondin motifs 13 (ADAMTS13) activity is low, with normal initial coagulation tests, which were compatible with a diagnosis of TTP. Interventions: After cessation of ticagrelor and initiation of therapeutic plasma exchange, our patient recovered. Outcomes: Re-administration of ticagrelor aggravated TTP and led the patient to death. Lessons: Clinicians should be aware of the possibility of ticagrelor-induced TTP in patients with a history of recent myocardial infarction; It is of crucial significance to discontinue and never reuse ticagrelor as long as it is suspected to be implicated in TTP.